PENERAPAN CASE-BASED REASONING UNTUK PENENTUAN LOKASI PEMASANGAN SMART ALARM KEBAKARAN - Sopiyan Dalis (LPPM STMIK ANTAR BANGSA, 2014)
Abstract— Fire is one of the concerns the citizens of Jakarta. In addition to causing substantial material damage, even hundreds of residents who are victims. One of the efforts made by the Jakarta administration is the installation of fire prevention equipment in fire-prone areas are connected via the telephone in the home residents with firefighters are smart alarm. But these efforts are constrained because there are several factors for the installation of smart alarms that are not met by the residents. This paper discusses the determination of the location of the installation of smart alarms to help firefighters wag to tackle the spread of fire to many houses. Taken from the cases determining the location of the previous installation of smart alarm as the experience for firefighters. Therefore, the implementation of the system of Case-Base Reasoning (CBR) to the Nearest Neighbor algorithm approach is most appropriate, because this system will take the experience from past cases similar to the value of proximity.